Increasing the Brand Awareness of PT. Erindo Mandiri’s Products through a Website - Jocelyn Liando (Institute of Research and Community Outreach - Petra Christian University, 2019)
A website is important because it would increase the brand awareness of a product or service for brand awareness is closely associated with promotional tool. The goal here is to promote and introduce the product or service of a business to the public. PT. Erindo Mandiri was established in 1990 as a manufacturer of mineral water. The main product of the company is Aquase mineral water that have different packaging - cups, bottles, and gallons. The main problem the company is facing is the low brand awareness of their products. The problems make only few people know about the products. This problem led PT. Erindo Mandiri to have a low-income rates problem. This inability is caused by the lack of appropriate tool used by the salesperson to explain and promote the products to agents and retailers. Therefore, the solution to PT. Erindo Mandiri is to improve or change the current website. This website can help the marketing staff to promote the company’s product more effectively to agents and retailers. Then, they will be attracted to buy our products and do partnership with the company. Keywords: brand awareness, promotional tools, company website.